Characterization of Old Nipah (Nypa fruticans Wurmb) Fruit Endosperm Flour and Its Application for Gluten-Free Cookies - Risa Nofiani; Jorion Romengga; Titin Anita Zaharah (agriTECH, 2021)
Old nipah fruit endosperms (ONFEs) contain high carbohydrates that have a potency to be applied to make flour. In this study, we made flour from ONFEF and its cookies. This study aimed to characterize the functional properties of unbleached and bleached old nipah fruit endosperm flour (UONFEF and BONFEF) and to assess the consumer acceptability of ONFEF flour and gluten-free cookies made from UONFEF and BONFEF. UONFEF and BONFEF were prepared from the ONFEs. They were cut, dried and ground, and sieved to obtain the UONFEF. TheUONFEF was bleached using Na2S2O5 0.4% for 15 mins then filtered, and the precipitates were dried under the sun. The dried precipitates were sieved to obtain the BONFEF. Both of the flour types were analyzed in terms of their functional properties (bulk density, swelling power, solubility, swelling capacity, water absorption index, and viscosity) and were used to make gluten-free cookies. The following ingredients were prepared to make the the gluten-free cookies: 200 g of flour (each of the UONFEF, BONFEF, and commercial wheat flour (CWF, Segitiga Biru brand) as a control), 100 g of margarine, 60 g egg, 125 g of fine granulated sugar, and 2 g of vanillin. Margarine, egg, and fine granulated sugar were mixed using a hand mixer and added with the flour, blended, molded, then baked. Consumer’s acceptability of each type of flour and cookies from different types of flour was evaluated using semi-trained panelists. The bleached treatment (the BONFEF) caused differences of the flour, particularly in terms of the physical properties (particle size, color, and odor) from the unbleached treatment and rated thehighest score for the overall criteria. Besides, the functional properties of the UONFEF were significantly different (p < 0.05) from those of the BONFEF except for the rendement, SP, and viscosity. The gluten-free cookie made from the UONFEF was the most preferred by the panelists. Therefore, the UONFEF can be successfully used as a substitute flour of wheat flour to make cookies.